Most outstanding committee chairman of the Philippine Marketing Association - Garcia, Leonardo R., Jr. (Animo Repository, 1997)
Marketing Management Department Chair Dr. Leonardo Garcia was cited Most Outstanding Committee Chairman of the Philippine Marketing Association (PMA) for 1996. As Chair of the Education-Seminars Committee of PMA, he was recognized for developing a series of quality seminars participated in by marketing practitioners nationwide.